Effects of Monosodium Glutamate (MSG) on Neuron Damages in Hippocampus in Sprague-Dawley rats - Rezania Razali; Zulkarnain Zulkarnain; Cynthia Wahyu Asrizal (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: Monosodium glutamate (MSG) is a flavor enhancer commonly used worldwide. Studies haveshown that high dose of MSG could act as neurotoxic or excitotoxic agent for neurons in the central nervoussystem. The aim of this study was to determine the effect of MSG on neuron changes of hippocampusanimalmodel.Materials and Methods: A total of 25 white male Sprague-Dawleyrats, aged 8-10 weeks,were dividedinto5 groups (2 control groups (i.e., none and solvent group) and3 treatment groups that received2, 4and 6 mg/gram MSG orallyfor 30 days). Afterfour weeks on treatment, all animals were sacrificed and the entire braintissueswere removed and immediately fixed in formalin for hematoxylin and eosin (H&E) staining.Results:The percentage of damaged neurons in three Cornuammonisareas of hippocampus was higher inanimal supplemented with MSG compared to controls. At the highest MSG concentration (6 mg/gram),52.1%, 55.2% and 66.0% of neurons from Cornuammonis 1, 2, and 3, respectively were damaged. Thepercentage of neuron damages in hippocampus was in dose-dependent manner.Conclusion: Our data suggested that high dose of MSG increased thehippocampus neuron damages in dosedependenteffect. This suggests the neurotoxicity effect of high dose of MSG.